Protein analysis of glioblastoma primary and posttreatment pairs suggests a mesenchymal shift at recurrence - Wood, Matthew D.; Reuss, David (Journal of neuropathology and experimental neurology, 2016)
Glioblastomas (GBM) are aggressive brain tumors that inevitably recur despite surgical resection, chemotherapy, and radiation. The degree to which recurrent GBM retains its initial immunophenotype is incompletely understood. We generated tissue microarrays of paired initial and posttreatment GBM (3 pairs positive and 17 negative for IDH1 R132H ) from the same patients and made comparisons in the IDH1 R132H -negative group for immunohistochemical and gene expression differences between primary and recurrent tumors. In initial tumors, immunopositivity for Ki-67 in > 20% of tumor cells was associated with shorter progression-free and overall survival. Recurrent tumors showed decreased staining for CD34 suggesting lower vessel density. A subset of tumors showed increased staining for markers associated with the mesenchymal gene expression pattern, including CD44, phosphorylated STAT3, and YKL40. Recurrent tumors with the greatest increase in mesenchymal marker expression had rapid clinical progression, but no difference in overall survival after second surgery. Comparison of protein and gene expression data from the same samples revealed a poor correlation. A subset of tumors (15%) showed loss of neurofibromin protein in both initial and recurrent tumors. These data support the notion that GBM progression is associated with a shift toward a mesenchymal phenotype in a subset of tumors and this may portend a more aggressive behavior.